1999
DOI: 10.1073/pnas.96.7.3616
|View full text |Cite
|
Sign up to set email alerts
|

Telomerase in kinetoplastid parasitic protozoa

Abstract: We have identified telomerase activity in extracts of three evolutionarily diverse kinetoplastid species: Trypanosoma brucei, Leishmania major, and Leishmania tarentolae. Telomerase activity was initially detected in extracts from insect form cells of all three kinetoplastid species by using a modification of the one-tube telomere repeat amplification protocol [Kim, N., et al. The activity in T. brucei extracts was sufficiently robust to enable its detection in a direct assay of telomerase; enzyme processivity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
51
0
5

Year Published

2000
2000
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(65 citation statements)
references
References 55 publications
3
51
0
5
Order By: Relevance
“…In TbTR-DKO cells expressing TbTRt mutant, most of the mutant telomeres only had a short stretch of mutant sequence incorporated, suggesting low processivity of T. brucei telomerase. This is consistent with our telomerase primer extension result and previous observations [28].…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…In TbTR-DKO cells expressing TbTRt mutant, most of the mutant telomeres only had a short stretch of mutant sequence incorporated, suggesting low processivity of T. brucei telomerase. This is consistent with our telomerase primer extension result and previous observations [28].…”
Section: Discussionsupporting
confidence: 83%
“…Therefore, altering the TbTR template sequence can have a profound effect on the telomere structure, which may have therapeutic implications. In addition, previous studies proposed a putative template domain for Trypanosoma telomerase RNA [28,38], which has a unique cytosine-rich motif distinctive from any other known TR molecules, except that from another pathogenic protozoa Plasmodium falciparum (Supplementary information, Figure S1A). Through mutation analysis, we confirmed that this motif indeed is part of TbTR template.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Transcriptionally active telomeres grow slightly faster (10 bp per cell division), suggesting a correlation between telomere structure and the transcriptional status of the genes located in their proximity [20]. Telomerase activity with limited processivity has been described in three species of kinetoplastids, including T. brucei [21]. In addition, position effects within the ES [22][23][24], and chromatin remodeling and developmentally regulated repression effects close to telomeres [16], suggest a role for telomeres in regulating antigenic variation and suggest that there are differences in telomeric chromatin structure between BF and PF trypanosomes.…”
Section: Introductionmentioning
confidence: 99%